Mediating Enduring Rivalry: Prospects For Indonesian Mediation Initiatives In The India-Pakistan Kashmir Dispute - Rahayu, Liska; Defrida Suzana Lukuaka; Zhafirah Azzahra Juniusyani; Ichsan Malik (CV. AFDIFAL MAJU BERKAH, 2024)
The enduring conflict over Kashmir between India and Pakistan remains unresolved despite several international mediation attempts. This study investigates these historical endeavors and evaluates Indonesia’s prospective role as a mediator leveraging its neutral stance and long-standing connections with both parties. A comprehensive qualitative literature review revealed that preceding mediations primarily concentrated on territorial lines, allocation of resources, and ephemeral ceasefires that temporarily eased tensions but were inadequate in addressing the underlying ideological divergences and identity issues perpetuating distrust. While frameworks such as the Indus Waters Treaty, which tackle joint technical concerns, have yielded some success in fostering collaborative arrangements, imposed resolutions have often lacked credibility due to sovereignty concerns and national rhetoric. The research findings indicate that Indonesia is posited as a potential neutral facilitator, drawing from its diplomatic accord and cultural rapport with India and Pakistan. Its non-aligned disposition, coupled with a track record of brokering peace within its region, uniquely qualifies it to sensitize dialogues and engineer technical partnerships inspired by its own experiences with autonomy accords. Although challenging, strategically implemented Indonesian-led confidence-building initiatives could gradually nurture mutual trust and cooperation. For the transformation of the Kashmir dispute to be enduring, it is recommended that a comprehensive strategy be adopted, placing a premium on reconciliation, inclusive policymaking, and the primacy of human security. Crucially, any process must incorporate localized reconciliation dialogues and bottom-up mechanisms to ensure legitimacy and resolve deep-seated grievances